Involvement of Y-Family DNA Polymerases in Mutagenesis Caused by Oxidized Nucleotides in Escherichia coli - Yamada, Masami (American Society for Microbiology, 2006)
Escherichia coli DNA polymerase IV incorporated 2-hydroxy-dATP opposite template guanine or thymine and 8-hydroxy-dGTP exclusively opposite adenine in vitro. Mutator phenotypes in sod/fur strains were substantially diminished by deletion of dinB and/or umuDC. DNA polymerases IV and V may be involved in mutagenesis caused by incorporation of the oxidized deoxynucleoside triphosphates.